Oxidative stress markers in canine parvovirus infection - Khoshvaghti, A; Baziyari, Ν; Dehghani, M; Vaziri, F (Journal of the Hellenic Veterinary Medical Society, 2024)
Parvovirus infections are among the deadly viral diseases in dogs and sick puppies. Young dogs are more prone to the virus. Antioxidants are important components of the defense system which prevent cell damage by neutralizing reactive oxygen species. Malondialdehyde is a reliable and commonly used marker of oxidative stress. The present study was performed to determine the role of oxidative stress markers in canine parvovirus disease. Thirty Cane Corso male dogs with an average age of 3-6 months were enrolled in this study out of which 10 animals were spontaneously infected with the parvovirus and the other 10 were healthy. The activity of superoxide dismutase (SOD), total antioxidant capacity (TAC), and malondialdehyde were measured by colorimetric methods whereas the enzymatic activity of glutathione peroxidase (GPX) was measured. Catalase was measured by means of rapid spectrophotometry and chromography was used for obtaining the concentrations of vitamin D and vitamin E. The increase in malondialdehyde in infected dogs demonstrates that oxidative stress plays a role in the pathogenesis of the parvovirus. The significant elevation in TAC, and lack of important changes in superoxide dismutase and catalase are indicative of a good response by the antioxidant system against oxidative stress induced by the parvovirus. In conclusion, oxidative stress is involved in the pathogenesis of parvovirus. Thus, strengthening the antioxidant system can be effective in the prevention and treatment of canine parvovirus infection.